Exploring the nexus between hypothyroidism and metabolic dysfunction-associated steatotic liver disease: a UK biobank cohort study - Haitao Wang; Changlin Zheng; Peisong Wang (Scientific Reports)
Abstract Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease characterised by lipid deposition in liver cells. The global prevalence of NAFLD has significantly increased from 8.2% in 1990 to 30.2% in 2023, establishing it as a growing public health concern. In recent years, the name NAFLD has been replaced by metabolic dysfunction-associated fatty liver disease (MASLD). Numerous observational studies have investigated the potential association between hypothyroidism and MASLD; however, the findings remain inconsistent. In this context, a systematic analysis was conducted to examine the relationship between hypothyroidism and MASLD using data from a large cohort within the UK Biobank. Utilising prospective data from the UK Biobank, a Cox proportional hazards model supplemented with multiple sensitivity analyses was applied to investigate the association between the incidence of hypothyroidism and the onset of MASLD. In addition, stratified analyses and prognostic assessments were performed to assess potential effect modifiers. To explore the underlying mechanisms, mediation analyses were conducted, along with restricted cubic spline regression, to examine potential non-linear relationships and mediation effects within this association. The study found that after fully adjusting for multiple covariates, the risk of MASLD in hypothyroidism patients was 1.711 times that of non-hypothyroidism patients (95% CI 1.560–1.877, P < 0.001). Both subtypes of hypothyroidism, namely non-surgical related hypothyroidism (NSRH) and surgical related hypothyroidism (SRH), were associated with a markedly elevated risk of MASLD onset. For NSRH, the risk is increased by 1.710 times (95% CI 1.557–1.878, P < 0.001), and for SRH, the risk is increased by 1.763 times (95% CI 1.344–2.313, P < 0.001). Stratified analysis revealed an interaction effect between gender and BMI in relation to the risk of MASLD among individuals with NSRH. Mediation analysis revealed the critical role of specific biomarkers in elucidating the relationship between hypothyroidism and MASLD. Notably, red cell distribution width, C-reactive protein, HbA1c, and total protein were identified as significant mediators in this association. Patients with hypothyroidism exhibit a significantly increased risk of developing MASLD, with inflammatory and metabolic markers playing a mediating role in this association. These findings suggest that individuals with hypothyroidism, particularly those with elevated levels of inflammatory markers, may be at heightened risk for MASLD. As such, enhanced clinical monitoring of liver function in these patients is recommended to facilitate early detection and intervention.